2019
DOI: 10.15171/jcs.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Illness Perception Correction - Based Educational Program on Quality Of Life and Self- Care in Patients with Heart Failure: a Randomized Controlled Trial

Abstract: Introduction: Because of the chronic nature of Heart Failure (HF), low Quality of Life (QoL) and poor self-care are prevalent among patients with HF. Thus, the aim of this study was to evaluate the effect of illness perception correction- based educational program on QoL,and self- care in patients with HF. Methods: In this randomized controlled trial, 78 eligible patients were included in the study from Rajaei Heart Center (Tehran, Iran) and randomly assigned into intervention and control group with 1:1 alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Trials in other conditions have illustrated that interventions aiming to promote positive illness perceptions and beliefs can lead to improvements in symptoms, self-management and quality of life [ 41–44 ], and studies in RA have shown that beliefs and illness perceptions are linked to adherence [ 45 , 46 ]. Given the intimate link between illness perceptions and outcomes in RA, demonstrated by this and other studies, interventions to improve the illness perceptions of patients with negative illness perceptions at treatment onset may have the potential to improve long-term outcomes through increased ability to adapt, better adherence to treatment and improvements in self-management, although randomized controlled trials are required to assess the efficacy of any such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Trials in other conditions have illustrated that interventions aiming to promote positive illness perceptions and beliefs can lead to improvements in symptoms, self-management and quality of life [ 41–44 ], and studies in RA have shown that beliefs and illness perceptions are linked to adherence [ 45 , 46 ]. Given the intimate link between illness perceptions and outcomes in RA, demonstrated by this and other studies, interventions to improve the illness perceptions of patients with negative illness perceptions at treatment onset may have the potential to improve long-term outcomes through increased ability to adapt, better adherence to treatment and improvements in self-management, although randomized controlled trials are required to assess the efficacy of any such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason might be the frequency of education. Previous studies adopted 30-40education sessions administered 3-4 times and showed significant improvement in the illness representations of patients with myocardial infarction or HF (Sadeghi Akbari et al, 2019;Sararoudi, Motmaen, Maracy, Pishghadam, & Kheirabadi, 2016). HF is a complex syndrome, and patients' decision-making can be affected by their day-to-day, real-world situations.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the effect of illness representation-focused interventions on illness representations and/ or self-care in patients with HF (Kordshooli, Rakhshan, & Ghanbari, 2018;Sadeghi Akbari, Cheraghi, Kazemnejad, Nomali, & Zakerimoghadam, 2019). Kordshooli et al (2018) examined the effect of a four-step family-centred empowerment model on the perception of the illness in patients with HF.…”
Section: Illness Representations Are Individuals' Perceptions and Belmentioning
confidence: 99%
“…1) According to the Center for Disease Control and Prevention statistics in Iran, approximately 3,400 per 100,000 individuals are diagnosed with heart failure in Iran, and these individuals experience the debilitating complications of heart failure. 2) Heart failure is a widely common cause of early hospitalization and readmission in patients aged >65 years. 3) There are no specific statistics on the prevalence of cardiovascular diseases in Iran, but mortality from heart disease has increased by approximately 20% to 45% according to several studies in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases are the number one cause of death in people aged >35 years in Iran [ 1 ]. According to the Center for Disease Control and Prevention statistics in Iran, approximately 3,400 per 100,000 individuals are diagnosed with heart failure in Iran, and these individuals experience the debilitating complications of heart failure [ 2 ]. Heart failure is a widely common cause of early hospitalization and readmission in patients aged >65 years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%